Submerged macrophyte self-recovery potential behind restoration treatments: sources of failure - Rybak, Michał; Rosińska, Joanna; Wejnerowski, Łukasz; Rodrigo, Maria A.; Joniak, Tomasz (Frontiers in Plant Science, 2024)
When exploring the challenges of restoring degraded lakes, we often do not observe the expected results despite executing all planned activities. Our study elucidates the reasons that impede the recovery of submerged macrophytes despite ameliorated light conditions. When prolonged lake degradation occurs, subsequent efforts to increase light availability often prove insufficient, resulting in a persistent turbid water state. In this study, we attempted to determine the reasons for these failures through a germination test and propagule bank analysis conducted in bottom sediments from a severely degraded lake, which underwent restoration. Although the bottom sediments indicate relative potential in the number of oospores and seeds, their germination efficacy remained dismally low. Based on the germination test results and factors affecting the development of submerged macrophytes (physical and chemical parameters, lake morphology, fish and waterfowl herbivory), we stated that improvement of light conditions in the lake could be insufficient to recover the vegetation, especially when the potential to renew diverse plant communities from sediments naturally is low. Our findings advocate for a paradigmatic shift in lake restoration strategies. A holistic approach that includes propagule bank assessments before embarking on restoration initiatives and enabling the identification of macrophyte resurgence potentials is recommended. We also advocate for a multifaceted restoration framework, emphasizing the indispensability of augmenting natural recovery mechanisms with targeted interventions. Consequently, in some cases, macrophyte reintroduction could be the only solution.By reintroducing autochthonic species to site-specific ecological dynamics, we anticipate an increased success rate in restituting submerged vegetation, thus catalyzing ecological regeneration within degraded lake ecosystems.